Implementasi Surah al-Hujurat Bagi Membendung Konflik dan Melestarikan Hubungan Baik di Tempat Kerja: The Application of Surah al-Hujurat in Mitigating Conflict and Sustaining Good Relationships in the Workplace - Yasir Ramlee (Maʿālim al-Qurʾān wa al-Sunnah, 2024)
Sustaining positive relationships in the workplace is a crucial challenge that demands careful consideration, as each employee has personal goals that may differ from those of their colleagues, potentially leading to conflicts. Uncontrolled conflicts resulting from strained relationships can have a clear negative impact on performance and work quality. Thus, well-defined guidelines are essential for enhancing workplace interactions and ensuring that all employees are aware of the ethical standards that must be upheld during their duties. This paper examines the implementation of various strategies in the workplace to foster and maintain positive relationships, drawing upon the interpretation of selected verses from Surah al-Hujurat. The guidelines outlined in this Surah emphasise the importance of respecting authority, adhering to ethical communication practices, promoting a culture of cooperation and self-reflection, and valuing diversity in character. By internalising these principles, the workplace can evolve into a more positive and productive environment, underpinned by mutual understanding and strong collaboration among employees.